PENGARUH MEDIA VIDEO ANIMASI TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SDN 06 SITIUNG - M. Anggrayni; Zumrotun Lutfiah; Sonia Yulia Friska; Rohana (STKIP Subang, 2024)
This research was motivated by the low learning outcomes of students. Based on the daily exams of class V students at SDN 06 Sitiung, the science learning content is still low. The aim of this research is to find out whether there is an influence on student learning outcomes taught using animated video learning media for class V at SDN 06 Sitiung for the 2023/2024 academic year. This is a matter of concern as to what is the causal factor for this. Animated video learning media on student learning outcomes is an interesting thing to solve the factors that cause the above problems. This research is a quantitative research with an experimental design in the form of a pre-experimental design type one group pretest-posttest (before and after treatment). The population of class V students at SDN 06 Sitiung and the sample of class V students at SDN 06 Sitiung is an experimental class that was given treatment before and after using animated video learning media. The data collection technique in this research was carried out using tests in the form of multiple choice questions. , this data was analyzed using the normality test and hypothesis testing. Based on the normality results, it can be concluded that the significance obtained from the pretest data is 1.59<0.05 and the significance obtained from the posttest data is 0.05<0.05. Hypothesis test results from the paired samples test can be obtained with a significant value of 0.000. The test results show a significant value of <0.05, namely 0.000<0.05. So the results of the paired samples test can be concluded that H0 is rejected and Ha is accepted. In using animated video learning media for science learning content, there is a significant influence on student learning outcomes before and after being treated in class V at SDN 06 Sitiung.